Observations on the morphology of the uterus of the porcupine (Hystrix cristata) - Ozdemir, Dervis; Atalar, Omer (Univ Zagreb Vet Faculty, 2009)
The uterine structure of the porcupine (Hystrix cristata) was examined grossly and microscopically. The uterus is composed of two narrow and convoluted uterine horns, separated by the velum uteri, a small uterine body and a long cervix. Following routine histological procedures, uterus tissue specimens were examined under light microscopy. The endometrial lining of both uterine horns and body was a pseudostratified, columnar ciliated epithelium. The endometrium contained sparse simple tubular glands. The animals in the luteal phase showed a more developed hyperplasia of the endometrial simple tubular glands than females in the follicular phase. The cervix presents interdigitated rows of mucosal prominences that project into the lumen.
Keywords: Hystrix cristata; porcupine; uterus; endometrial epithel